Catholic Intellectuals and Conservative Politics in America, 1950-1985 - Allitt, Patrick (Cornell University Press, 2019)
At the end of World War II, conservatism was a negligible element in U.S. politics, but by 1980 it had risen to a dominant position. Patrick Allitt helps explain the remarkable growth of the contemporary conservative movement in the light of Catholic history in the United States. Allitt focuses on the role of individual Catholics against a backdrop of volatile cultural change, showing how such figures as William F. Buckley, Jr., Garry Wills, John T. Noonan, Jr., Michael Novak, John Lukacs, Thomas Molnar, Russell Kirk, Clare Boothe Luce, Ellen Wilson, Charles Rice, and James McFadden forged a potent anti-liberal intellectual tradition. Catholic Intellectuals and Conservative Politics in America, 1950-1985 is much more than a history of conservative Catholics, for it illuminates critical themes in postwar American society. As Allitt narrates the interplay of liberal and conservative politics among Catholics, he unfolds a history both intricate and sweeping. After describing how New Conservatism was shaped in the 1950s by William F. Buckley, Jr., and an older generation of Catholic thinkers including Ross Hoffman and Francis Graham Wilson, Allitt traces the range of Catholic responses to the cataclysmic events of the 1960s: the election ofJohn F. Kennedy, the civil rights movement, the decolonization of Africa, Supreme Court decisions on school prayer, the war in Vietnam, and nuclear arms proliferation. He shows how the transformation of the Church prompted by the Second Vatican Council not only intensified existing divisions among Catholics but also shattered the unity of the Catholic conservative movement. Turning to the 1970s, Allitt chronicles bitter controversies concerning family roles, contraception, abortion, and gay rights. Next, comparing the work of John Lukacs, Thomas Molnar, Garry Wills, and Michael Novak from the 1950s through the 1980s, Allitt demonstrates how individual Catholic conservatives drew different lessons from similar contingencies. He concludes by assessing recent ideological shifts within American Catholicism, using as his test case the conservative resistance to the Catholic Bishops' 1983 Pastoral Letter on Nuclear Weapons. Offering new insight into the subtle interplay between religion and politics, Catholic Intellectuals and Conservative Politics in America, 1950-1985 will be engaging reading for everyone interested in the postwar evolution of American politics and culture.